2023
DOI: 10.25251/skin.7.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Clinician- and Patient-Reported Outcomes with Tirbanibulin 1% Treatment for Actinic Keratosis in Routine Clinical Practice Across the U.S. (PROAK Study)

Abstract: Background: Patients' experiences regarding topical actinic keratosis (AK) treatments may optimize clinical outcomes. PROAK study aimed to evaluate patient- and clinician-reported outcomes among adult patients with AK on face or scalp who were prescribed tirbanibulin in real-world clinical practice in the United States. Methods: Key primary endpoint was quality of life (QoL) assessed by Skindex-16. Additional endpoints were tirbanibulin treatment effectiveness and satisfaction (Treatment Satisfaction Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In another study of clinician-and patient-reported outcomes, 73.9% of patients and 89.2% of clinicians felt that tirbanibulin had a shorter duration of skin reactions than previous field treatments. 28 Additionally, 91% of clinicians and 76.6% of patients reported that tirbanibulin had milder skin reaction severity than prior field treatments. 28 The tolerability of tirbanibulin makes it more likely that patients will be compliant with therapy and effectively eradicate their AKs.…”
Section: Statement 7: When Assessing the Overall Efficacy Of Treatmen...mentioning
confidence: 99%
See 2 more Smart Citations
“…In another study of clinician-and patient-reported outcomes, 73.9% of patients and 89.2% of clinicians felt that tirbanibulin had a shorter duration of skin reactions than previous field treatments. 28 Additionally, 91% of clinicians and 76.6% of patients reported that tirbanibulin had milder skin reaction severity than prior field treatments. 28 The tolerability of tirbanibulin makes it more likely that patients will be compliant with therapy and effectively eradicate their AKs.…”
Section: Statement 7: When Assessing the Overall Efficacy Of Treatmen...mentioning
confidence: 99%
“…28 Additionally, 91% of clinicians and 76.6% of patients reported that tirbanibulin had milder skin reaction severity than prior field treatments. 28 The tolerability of tirbanibulin makes it more likely that patients will be compliant with therapy and effectively eradicate their AKs. 1485 can be very effective, only field-directed therapy is able to treat subclinical lesions and reduce FC.…”
Section: Statement 7: When Assessing the Overall Efficacy Of Treatmen...mentioning
confidence: 99%
See 1 more Smart Citation